Life Expectancy at Birth: the Numbers Behind the Means - Zijdeman, Richard Lindert (TSEG - The Low Countries Journal of Social and Economic History, 2017)
Datasets spanning long periods of time, are crucial to our understanding of a range of phenomena, both within as outside social and economic history. For various processes, from social inequality to climate change, only change gradually, requiring long periods of time to observe and to explain change. Moreover, data spanning longer periods of time help us to unravel causality issues in the processes we study. Finally, time series data help us put contemporary phenomena in perspective.